Convex characterization of linearly convex domains - Nikolov, Nikolai; Thomas, Pascal J. (MATHEMATICA SCANDINAVICA, 2012)
We prove that a $C^{1,1}$-smooth bounded domain $D$ in $C^n$ is linearly convex if and only if the convex hull of any two discs in $D$ with common center lies in $D$.